The Use of Metabolomics Approach in The Combination With Multivariate Data Analysis For The Identification of Non-Halal Meats A Narrative Review - Abdul, Rahman; Vevi, Maritha; Anjar, Windarsih; Muhammad Jefriyanto, Budikafa; Florentinus Dika, Octa Riswanto; Muhammad Abdurrahman, Munir; Halida, Rahmania (Korean Society for Food Science of Animal Resources (KoSFA), 2025)
There are three issues in relation to halal products namely raw materials, processes, and halal authentication analysis. One of the issues encountered in raw materials is meat origins which can be obtained either form its sources (halal and non-halal meats) or due to slaughtering processes (Zabiha and non-zabiha). Therefore, some scientist tried to develop analytical methods capable of discriminating the types of halal and non-halal meats due to its sources and its slaughtering processes. Three approaches have been introduced for the identification and quantification of nonhalal meats, namely identification of specific markers, profiling using fingerprinting tools and metabolomics studies. Differentiation of halal and non-halal meats from the perspectives of its sources and slaughtering processes are very challenging. This review highlighted the application of analytical methods based on metabolomics approaches in combination with chemometrics for differentiation of halal and non-halal meats from its sources such as rat meat, pork, canine meats, and from the slaughtering processes in terms of Zabiha and non-zabiha procedures.